Optimalisasi Sistem Informasi Manajemen Puskesmas (SIMPUS) dalam Mendukung Pengambilan Keputusan Manajerial di UPTD Puskesmas Tanjungpandan - Putri Permata Sari; Tulas Novalima; Fatimah Muthmainnah; Eka Indah Wahyuni; Hafizd Ardiansyah (JUKI : Jurnal Komputer dan Informatika, 2025)
The purpose of this study was to determine the Optimization of the Puskesmas Management Information System (SIMPUS) in Supporting Managerial Decision Making at UPTD Puskesmas Tanjungpandan. The Puskesmas Management Information System (SIMPUS) plays an important role in improving the efficiency of health services at the puskesmas level. This study aims to review the implementation of SIMPUS at UPTD Puskesmas Tanjung Pandan, Belitung City, by analyzing aspects of effectiveness, constraints, and their impact on health services. The method used was a descriptive qualitative approach with interviews and observations as data collection techniques. The results of the study show that the Puskesmas Management Information System (SIMPUS) at the UPTD Puskesmas Tanjungpandan has a crucial role in improving the efficiency of health services and supporting data-based managerial decision making. With an integrated system, patient data processing, resource management, and medical personnel performance evaluation can be done more quickly and accurately. Although there are challenges in implementation, such as technology infrastructure and HR training, solutions such as improving data quality, information security, and collaboration between various parties can optimize the benefits of SIMPUS. With continued support, this system has the potential to become a key foundation in improving the quality of health services and the effectiveness of puskesmas management in the future.